Peranan Modal Sosial Dalam Praktik Lamaran Masyarakat Desa Sumberbendo Kecamatan Mantp Kabupaten Lamongan - Nur, Firda; Harianto, Sugeng (Paradigma, 2023)
Abstract Researchers are interested in researching the role of social capital in the application practice of the Sumberbendo village community, Mantup District, Lamongan Regency. Indonesia is dubbed as a multicultural society, one of the unique phenomena is the practice of women applying to men, but it is suspected that due to the influence of globalization such as education and technology there is a cultural shift regarding the application practice. The purpose of this study is to identify the role of social capital and community application practices in Sumberbendo Village. This study uses a qualitative descriptive method, with the perspective of Pierre Bourdieu's social capital theory. The results of this study found that the practice of women proposing to men is carried out when the prospective bride is a native of the village of Sumberbendo. If the potential partner comes from outside the Sumberbendo village community, then the tradition of women proposing to men does not apply. This is due to cultural differences in each prospective bride and groom so that there is an adjustment and respect for the culture of the prospective partner. The role of social capital in application practice is very important in determining a potential spouse or son-in-law. Social capital is taken into consideration in choosing a potential partner or son-in-law including seeds, bebet, weight. In addition, the education of the prospective partner is also a consideration. Taking religious education through Islamic boarding schools is one of the considerations in choosing a potential partner. This is because the Sumberbendo village community is a santri community, where they look highly on the Kyai's family and someone who graduated from an Islamic boarding school. Keywords: Marriage Proposal Practice, Social Capital, Shift Abstrak Peneliti tertarik meneliti mengenai peranan modal sosial dalam praktik lamaran masyarakat desa Sumberbendo kecamatan Mantup kabupaten Lamongan. Indonesia dijuluki sebagai masyarakat multikultural, salah satu fenomena yang unik adalah praktik perempuan melamar laki-laki, namun karena pengaruh arus globalisasi seperti pendidikan dan teknologi adanya pergeseran pada praktik lamaran tersebut. Tujuan pada penelitian ini adalah mengidentifikasi peranan modal sosial dan praktik lamaran masyarakat di Desa Sumberbendo. Penelitian ini menggunakan metode deskripstif kualitif, dengan perspektif teori modal sosial Pierre Bourdieu. Hasil penelitian ini menemukan bahwa, praktik perempuan melamar laki-laki dilakukan ketika calon mempelai merupakan masyarakat asli desa Sumberbendo. Jika calon pasangan berasal dari luar masyarakat desa Sumberbendo, maka tradisi perempuan melamar laki-laki tidak berlaku. Hal ini karena perbedaan budaya pada masing-masing calon mempelai sehingga terjadi penyesuaian dan menghargai budaya calon pasangan. Adapun peran modal sosial dalam praktik lamaran sangat penting dalam menentukan calon pasangan atau menantu. Modal sosial menjadi bahan pertimbangan dalam memilih calon pasangan atau menantu meliputi bibit, bebet, bobot. Selain itu, pendidikan calon pasangan juga menjadi pertimbangan. Menempuh pendidikan agama melalui pondok pesantren menjadi salah satu pertimbangan dalam memilih calon pasangan. Hal ini karena masyarakat desa Sumberbendo merupakan masyarakat santri, dimana memandang tinggi keluarga Kyai dan seseorang lulusan pondok pesantren. Kata Kunci: Praktik Lamaran Masyarakat, Modal Sosial, Pergeseran.